(untitled) (Mustansiria Dental Journal, 2018)
The prevalence of metabolic syndrome (MetS) is increasing worldwide, and it appears to increase independently the risk of cardiovascular disease. Periodontitis has been shown to have an association with the risk of cardiovascular disease. The aim of the present study is to investigate the association between periodontal status and the main components of metabolic syndrome, singly, and in combination in type 2 diabetic patients. One hundred and seventy five patients (96 males and 79 females) with type 2 diabetes mellitus (T2DM) were enrolled in the study. The following clinical characteristics were reported: age and gender, body mass index (BMI) and blood pressure. Periodontal status was assessed using periodontal disease index which includes plaque, calculus, and periodontal component of the index. An assessment of serum lipid analytes included estimation of serum triglycerides (TG) and serum high density lipoprotein cholesterol (HDL-C). There was a significant difference in mean value of periodontal disease index (PDI) between normotensive and hypertensive diabetic patients (3.31±0.83 vs. 3.82±0.65, P<0.001). Also there was a significant difference in PDI between normal and high TG groups (3.49±0.73 vs. 3.81±0.61, P<0.01). There was a significant increase in TG level in hypertensive compared to normotensive diabetic patients (P<0.01). Only in presence of hypertension and obesity in addition to diabetes that PDI was significantly increased in comparison with diabetic hypertensive non obese patients (4.1±0.58 vs. 3.62±0.64, P<0.001). There were no significant differences in TG level between obese and non obese diabetic patients while there was a significant increase in TG level in patients who were hypertensive obese compared to normotensive non obese (174.64 ±61.39 vs. 150.80±54.96 respectively, P<0.05). Presence of two or more characteristics of MetS has resulted in a significant increase of PDI when compared with patients who had only diabetes (P<0.001). In conclusion, hypertension and hypertriglyceridemia as main components of MetS are singly associated with periodontitis in T2DM and the presence of any two studied components of MetS in addition to diabetes will attain the worst deterioration in periodontal status.